User Interface Preferences in the Design of a Camera-Based Navigation and Wayfinding Aid. (March 2013) - Arditi, Aries; Tian, YingLi
Introduction: Development of a sensing device that can provide a sufficient perceptual substrate for persons with visual impairments to orient themselves and travel confidently has been a persistent rehabilitation technology goal, with the user interface posing a significant challenge. In the study presented here, we enlist the advice and ideas of individuals who are blind with respect to this challenge, for an envisioned camera-based aid to navigation and wayfinding. Methods: We administered a short questionnaire about user preferences and needs for such a device to a sample of 10 well-educated, employed (or retired) visually impaired participants with light perception or less, who were familiar and comfortable with assistive technology. Generally, the items were rankings of relative priority. Results: Participants preferred speech as a communications medium for navigating the environment; preferred controlling the auditory display by querying the system rather than interacting via a menu or receiving a stream of continuous speech; and preferred providing input to the system through a keypad rather than through a voice recognition system. Architectural features such as doors and stairs were ranked the most important environmental objects to be located with such a device (over furniture, persons, personal items, and even text signs). Discussion: Our sample reported a desire for devices that can guide them to architectural features of their environment. They appear to prefer device interfaces that give them control, and would rather query a system than interact with a menu. They prefer unobtrusive input on a device via keypad rather than through voice recognition. Implications for practitioners: Designers of camera-based navigation devices may wish to consider the preferences of our sample by incorporating a query-based interface with simple keypad input and speech output, and to include in their object recognition efforts the goal of identifying architectural features that are significant to users who are blind in navigation.